Penerapan Metode Pembelajaran Dakwah Terhadap Peningkatan Karakter Peserta Didik SMP Negeri 7 Kota Makassar - RS, Austina Damayanti; Setiawati, Nur; Surani, Surani; Bunyamin, Andi; Nengsih, Ratika (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study aims to determine the development of students' character through Islamic Religious Education learning with the da'wah method in class VIII.1 of SMP Negeri 7 Makassar, teacher efforts in developing character, inhibiting factors, and out-of-class programs that support character development. This study uses a qualitative approach with observation, interview, and documentation techniques. The results of the study indicate that students' characters experience positive changes, such as honesty, discipline, and responsibility, with discipline having the highest percentage (81.81%) and hard work the lowest (51.51%). Teachers try to instill character through the habituation of positive values. Inhibiting factors include lack of awareness, motivation to learn, and student responsibility. The supporting programs outside the classroom include Scouts, OSIS, RPM, English, Paskibra, and Football. This study concludes that the da'wah method is effective in shaping students' character gradually